2019
DOI: 10.1039/c9md00297a
|View full text |Cite
|
Sign up to set email alerts
|

Derivatisation of parthenolide to address chemoresistant chronic lymphocytic leukaemia

Abstract: A parthenolide-derivative with favourable pharmacokinetic properties and good activity against drug-resistant chronic lymphocytic leukaemia is reported.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 127 publications
1
14
0
Order By: Relevance
“…The alamarBlue® assay was employed to measure their in vitro anti-leukaemic and LC 50 values were determined using CalcuSyn (Biosoft) software, Table 3 . The LC 50 values of parthenolide ( 1 ), 2a and 2b are consistent with previously published reports ( Table 3 , 4.6, 3.4 and 5.3 μM, entries 1, 2 and 3 respectively) [ 9 ]. The most active aniline derivatives were phenol-containing 3b , 3c and 3o LC 50 values of 12.5, 11.7 and 12.9 μM respectively ( Table 3 , entries 5, 6 and 18).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The alamarBlue® assay was employed to measure their in vitro anti-leukaemic and LC 50 values were determined using CalcuSyn (Biosoft) software, Table 3 . The LC 50 values of parthenolide ( 1 ), 2a and 2b are consistent with previously published reports ( Table 3 , 4.6, 3.4 and 5.3 μM, entries 1, 2 and 3 respectively) [ 9 ]. The most active aniline derivatives were phenol-containing 3b , 3c and 3o LC 50 values of 12.5, 11.7 and 12.9 μM respectively ( Table 3 , entries 5, 6 and 18).…”
Section: Resultssupporting
confidence: 92%
“…Inspired by the work of Neelakantan et al . in identifying compound 2a as a promising NF-κB inhibitor [ 28 ], the co-authors of this report had previously identified compound 2b as a potential anti-CLL therapy [ 8 , 9 ], which showed improved drug metabolism and pharmacokinetics (DMPK) properties. To the best of our knowledge the anti-leukaemic activity of aniline-derivatisation on parthenolide has not previously been addressed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations